To Spray or Not to Spray? Pesticides, Banana Exports, and Food Safety - Wilson, John S. (World Bank, Washington, D.C., 2013)
How governments regulate food safety and environmental protection, including pesticide residue levels, has important implications for trade. The World Trade Organization (WTO) Ministerial held in Doha, Qatar in November 2001, included statements on standards, and their impact on market access for developing countries. These issues will continue to be important in trade policy dialogues. It is assumed - and evidence from recent analysis confirms - that food safety standards can affect the ability of agricultural producers to meet regulatory standards, set by importing countries. The authors explore a fundamental question in food safety and environmental standards: Do regulations on pesticide have an effect on trade? They examine regulatory data from 11 OECD importing countries, and trade data from 19 exporting countries. The results suggest that a 10 percent increase in regulatory stringency - tighter restrictions on the pesticide chlorpyrifos - leads to a decrease in banana imports by 14.8 percent. This represents a significant impact on trade, and affect prospects of developing countries who continue to rely on exports of agricultural commodities, such as bananas. The findings also suggest that the lack of consensus on international standards, and divergent national regulations on pesticides is costly. For example, the authors estimate that if the world were to adopt a standard at a level of regulatory stringency suggested by Codex (the body charged with setting global standards in this area), in contrast with one set at the level in place in the European Union, there would be a U$S 5.3 billion loss in world exports.